2010
DOI: 10.1021/ol100619p
|View full text |Cite
|
Sign up to set email alerts
|

Bis-Anthracene Fused Porphyrins: Synthesis, Crystal Structure, and Near-IR Absorption

Abstract: Synthesis of fused bis-anthracene porphyrin monomers and dimers has been achieved by oxidative ring closure using FeCl(3) and Sc(OTf)(3)/DDQ, respectively. The fused compounds display red-shifted absorption spectra with maxima in the near-IR at 973 and 1495 nm, respectively, and small electrochemical HOMO-LUMO gaps. The crystal structure of the fully fused bis-anthracene porphyrin shows that it has a regular planar pi-system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
80
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(84 citation statements)
references
References 33 publications
1
80
0
3
Order By: Relevance
“…These analyses revealed 1 a to be a single compound. [13] Variable-temperature 1 H NMR measurements from 193 to 353 K did not show any significant change. Figure 1) were observed at 6.96 and 9.12 ppm, and 7.76 and 9.02 ppm, respectively in the 1 H NMR spectrum of 1 a in [D 2 ]tetrachloroethane at 353 K ( Figure 1).…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…These analyses revealed 1 a to be a single compound. [13] Variable-temperature 1 H NMR measurements from 193 to 353 K did not show any significant change. Figure 1) were observed at 6.96 and 9.12 ppm, and 7.76 and 9.02 ppm, respectively in the 1 H NMR spectrum of 1 a in [D 2 ]tetrachloroethane at 353 K ( Figure 1).…”
mentioning
confidence: 89%
“…[13] The precursor 3 was prepared in 54 % yield by the lithiation of 9-bromobis(mesityloxy)anthracene 4 [13] with nBuLi, followed by treatment with dibromodiborapentacene 5. Bulky mesityloxy substituents are introduced at the 4,5-positions of the anthracene moieties for the cyclization to occur selectively at the 1,8-positions and to prevent the strong aggregation of the resulting PAH p skeleton.…”
mentioning
confidence: 99%
“…In einer Eintopfreaktion entstanden hier sieben neue Bindungen. Das Ergebnis ist ein brettartiger Farbstoff mit ausgedehntem p‐System und langwelliger Absorption im nahen IR‐Bereich (ëmax = 1495 nm) 44…”
Section: Tetrapyrroleunclassified
“…However, significant achievements have only been made recently. [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] For example, Campbell et al [16] linked a penta-2,4-dienoic acid group to the β-pyrrolic position of a zinc porphyrin and an energy conversion efficiency of 7.1 % was achieved as a result of efficient electronic coupling of the porphyrin to TiO 2 through a conjugated linker. Imahori and coworkers [4,6,11,18,19] found that bulky mesityl groups can reduce aggregation.…”
Section: Introductionmentioning
confidence: 99%